2021
DOI: 10.1159/000514443
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Immune Prognostic Index May Predict the Efficacy of Different Treatments in Patients with Advanced NSCLC: A Meta-Analysis

Abstract: Background: Our purpose was to evaluate the predictive value of the lung immune prognostic index (LIPI) in patients with advanced non-small cell lung cancer (NSCLC) receiving different treatments. Methods: A systemic literature search of major databases of medicine was performed to explore the association of LIPI with different therapeutic effects in patients with advanced NSCLC, with overall survival (OS) as the surrogate marker. As such, HR and 95% CI were simultaneously selected to evaluate such an associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…To our knowledge, only Xie et al. have published a meta-analysis about the relationship between the LIPI and efficacy of different treatments in NSCLC patients ( 38 ). In this article, there were only four studies included.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only Xie et al. have published a meta-analysis about the relationship between the LIPI and efficacy of different treatments in NSCLC patients ( 38 ). In this article, there were only four studies included.…”
Section: Discussionmentioning
confidence: 99%
“…Another pooled analysis of 5 randomized trials evaluating ICIs versus CT only and 6 randomized trials evaluating targeted therapies (TTs) versus other TTs or CT only concluded also that the LIPI was prognostic in all the cohorts (1368 patients treated with ICIs and 1072 patients treated with CT only for the trials evaluating ICIs; 1110 patients treated with TTs and 437 patients treated with CT only for the trials evaluating TTs) [ 41 ]. A meta-analysis published a few years later finally concluded that the LIPI was prognostic, independent of the treatment [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that poor LIPI correlated with lower odds of achieving disease control (OR = 0.44; p = 0.005). An available meta-analysis of four clinical trials involving a total of 7373 patients with NSCLC receiving immunotherapy, targeted therapies, or chemotherapy demonstrated that LIPI groups can be effectively used to determine prognosis [ 31 ]. The LIPI groups predicted OS both in patients treated with immunotherapy and in those treated with targeted therapies or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%